Values, Identity, and Sustainable Development in Africa
XI, 332 p.
Keywords: This book contends that Africa’s sustainable development must be built on African identity and values. Contributors reflect of the role of values in Africa’s effort to overcome poverty, the focus of SDG 1. The volume reflects on how indigenous values such as Ubuntu constitute a critical resource in addressing poverty. It reiterates the importance of positioning the response to poverty in Africa on the continent’s own, home grown values. Contributors also interrogate how values such as integrity, hard work, tolerance, solidarity, respect and others serve to position Africa strategically to overcome poverty. The volume focuses on how values can help Africa to overcome challenges such as corruption, violence, intolerance, competitive ethnicity, xenophobia, misplaced priorities and others. It provides fresh and critical reflections on the role of values and identity in anchoring Africa’s development in the light of SDG 1. Ezra Chitando is a Professor of History of Religions at the University of Zimbabwe and Theology Consultant on HIV for the World Council of Churches. Eunice Kamaara is Professor of Religion at Moi University, Eldoret, Kenya.